Readings in Educational Administration (Washington, D.C. : Distributed by ERIC Clearinghouse, 1991)
Findings of a study to determine which books are recommended as required readings for educational administration students are presented in this paper. Surveys were mailed to 275 educational administration department chairs, asking them to list up to 10 books other than textbooks suitable for required graduate reading. Fifty-five completed surveys were returned. Of the 308 titles submitted, little agreement existed among respondents. A Cochran Q test determined statistical differences among the surveys according to the type of graduate degree offered by the institution. A list of 22 titles was developed for each of the following categories of institutions: overall; master's/education specialist; and doctoral granting. Five titles appear on all three lists. The list of 22 titles is recommended as a basic library of readings for students in educational administration/leadership. Five tables are included. (24 references) (LMI)
Includes bibliographical references and index.
Microfiche.
Keywords: Administrator Education; Books; Curriculum Development; Degree Requirements; Educational Administration; Elementary Secondary Education; Higher Education; Information Sources; Reading Material Selection; Reading Materials; Speeches/Meeting Papers; Reports, Research